SMEs and ICTs adoption: a new challenge to Regional Policies - António Soares; Gonçalo Santinha (European Regional Science Association (ERSA), 2004)
Information and Communication Technologies (ICTs) and their widespread have produced profound changes at economic and social levels. We are now in what is known as Information Society. The ways in which people, firms, institutions and governments deal with ICTs and understand their impacts is an important issue. One of the main characteristics of Information Society is the growing competition between agents through innovation. By innovation we mean the capacity to manage creatively the knowledge as an answer to changes in social needs and in technology. Hence, innovation occurs as a means of competitive advantage. The paper addresses this issue by highlighting the importance of innovation for Small and Medium Enterprises (SMEs), which are by far the most relevant actors in European Economy. It is argued that the access and use of information as well as the existence of interaction between agents are key factors for innovation. ICTs, if used in a correct and efficient matter, can play an important role by inducing and help SMEs to innovate. In spite of helping firms overcoming a wide range of barriers, the adoption and the search for efficiency in ICTs use can however become a problem. This is even more significant concerning SMEs and particularly those located in peripheral regions. In fact, acknowledging the existence of a regional digital divide and a digital divide by company size, the European Commission is developing several actions in order to face and overcome these problems. The paper addresses several initiatives undertaken by the European Commission since the Lisbon summit at March 2000. More recently, the European regional policies have changed from simply getting SMEs connected to the Internet to the effective integration of ICTs into business processes. As a conclusion, the authors argue that Digital Policies should take into account that ICT adoption and use by SMEs, cannot be regarded as a panacea to solve the problems of firms and regional development. Regional policies to help SMEs to adopt ICT must be integrated (in a coherent way) within broader regional strategies.
Keywords: 330